miR-21a-5p Contributes to Porcine Hemagglutinating Encephalomyelitis Virus Proliferation via Targeting CASK-Interactive Protein1 In vivo and vitro - Lv, Xiaoling; Zhao, Kui; Lan, Yungang; Li, Zi; Ding, Ning; Su, Jingjing; Lu, Huijun; Song, Deguang; Gao, Feng; He, Wenqi (Frontiers in Microbiology, 2017)
Porcine hemagglutinating encephalomyelitis virus (PHEV) is a highly neurovirulent coronavirus that can cause nervous symptoms in piglets with muscle tremors, hind limb paralysis and nystagmus. Whether some factors affect virus replication and proliferation had not been fully understood in the course of nerve damage caused by PHEV infection. In recent years, some reports suggested that miRNA might play a key regulatory role in viral infection. In this study, we found the miR-21a-5p is notably up-regulated in the brains of mice and N2a cells infected with PHEV, and it down-regulated the expression of CASK-interactive protein1 (Caskin1) by directly targeting the 3’-UTR of Caskin1 using a Dual-Luciferase reporter assay. The over-expression of miR-21a-5p or Caskin1 knockdown in the host significantly contributes to PHEV proliferation. Conversely, the silencing of miR-21a-5p by miR-21a-5p inhibitors suppressed the virus proliferation. Taken together, our results indicate that Caskin1 is the direct target gene of miR-21a-5p, and it is advantageous to virus proliferation by down-regulating Caskin1. These findings may help in the development of strategies for therapeutic applications.